Early results of ultrasonic aortic valve decalcification - Todurov, B. M.; MarkovetsА. V.; Zograbyan, A. R.; Demyanchuk, V. B. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The manuscript represents the results of surgical treatment for 40 patients with aortic valve stenosis with calcinosis. All patients underwent valve sparing procedure – ultrasonic aortic valve decalcification. Immediately after the procedure systolic pressure gradient was decreased and aortic valve area was increased significantly. Results can indicate about the effectiveness of surgery for such kind of patients.